AN INVESTIGATION INTO SOME MISCONCEPTIONS ABOUT MASS AND VOLUME BY JUNIOR SECONDARY SCHOOL LEARNERS IN ESWATINI - Olayinka, Adesola Afolayan (IJRDO -JOURNAL OF MATHEMATICS, 2023)
Mass and Volume are important fundamental concepts in Mathematics and they are normally introduced at the Junior Secondary School level across Swaziland. However, simple as the concepts appear to be, it has been observed, as presented in recent annual diagnostic reports, that learners repeatedly make some errors informed by their misconception about these measurements. This paper investigates the causes of the common errors with a view to arresting the trend. 200 students and 15 science teachers were randomly selected from 5 secondary schools in Manzini region as a representation of the other three regions in Swaziland. A combination of cluster sampling and rating scale analysis was employed. Responses collected from questionnaires administered in the course of the work were thoroughly analyzed and interpreted. Some recommendations were also suggested.